An integrated view of the methane system in the pockmarks at Vestnesa Ridge, 79°N - Panieri, Giuliana; Bünz, Stefan; Fornari, Daniel J.; Escartin, Javier; Serov, Pavel; Jansson, Pär; Torres, Marta E.; Hong, Wei-Li; Sauer, Simone; Garcia, Rafael; Gracias, Nuno (Marine Geology, 2017)
Accepted manuscript version. Published version available at https://doi.org/10.1016/j.margeo.2017.06.006 . Accepted manuscript version, licensed CC BY-NC-ND 4.0. The Vestnesa Ridge is a NW-SE trending, ~ 100 km-long, 1–2 km-thick contourite sediment section located in the Arctic Ocean, west of Svalbard, at 79°N. Pockmarks align along the ridge summit at water depths of ~ 1200 m; they are ~ 700 m in diameter and ~ 10 m deep relative to the surrounding seafloor. Observations of methane seepage in this area have been reported since 2008. Here we summarize and integrate the available information to date and report on the first detailed seafloor imaging and camera-guided multicore sampling at two of the most active pockmarks along Vestnesa Ridge, named Lomvi and Lunde. We correlate seafloor images with seismically defined subseafloor structures, providing a geological and ecological context to better understand pockmark formation. Subbottom and seismic surveys, water column imaging, geochemical data and seafloor observations indicate ongoing fluid flow at these pockmarks. Visual inspection and sampling using a high-resolution deep-sea camera and multicorer system show exposed gas hydrate and authigenic carbonate in association with biota within two of these pockmarks. Distributed methane venting at both Lomvi and Lunde supports extensive chemosynthetic communities that include filamentous sulfide-oxidizing bacteria and siboglinid tubeworms, all of which utilize chemical energy provided by the seeping fluids. Focused venting forms shallow gas hydrate, and sustains localized gas discharge from 50-m wide pits within the pockmarks. Cycles of carbonate precipitation and/or exhumation of carbonate deposits are indicated by scattered blocks of various size, pavements, and massive carbonate blocks up to 3 m high. Consistent with other observations along continental margin settings, we show that the extensive authigenic carbonate deposits in the Vestnesa pockmarks represent an important and prolonged methane carbon sink ...